De/Re-constructing Area 2 and the Shopping Center a linguistic landscape analysis - De Leon, John Michael O.; Saqueton, Grace M. (Quezon City College of Arts and Letters, University of the Philippines Diliman, 2018)
This research examines the signs in the facade or storefronts of dining places in Area 2 and the Shopping Center, UP Diliman to show how ethnolinguistic identity of the space is constructed through its linguistic landscape. This has been done by using Scollon and Scollon's principles of place semiotics, Blommaert's concept of "scale," and Hymes' concept of "setting." Upon analysis of the data, it is revealed that there is a correlation between the linguistic landscape and the ethnolinguistic identity of the space. The way the signs are constructed and adjusted reflects the sociolinguistic composition of the language groups, their assumed level of education, and the space's environmental conditions.
Thesis (B.A. in English Studies : Language)--University of the Philippines Diliman
Includes bibliographical references and appendices.